An integrative review of information systems and terminologies used in local health departments. (13th September 2013) - Olsen, Jeanette; Baisch, Mary Jo
Abstract: Objective The purpose of this integrative review based on the published literature was to identify information systems currently being used by local health departments and to determine the extent to which standard terminology was used to communicate data, interventions, and outcomes to improve public health informatics at the local health department (LHD) level and better inform research, policy, and programs. Materials and methods Whittemore and Knafl's integrative review methodology was used. Data were obtained through key word searches of three publication databases and reference lists of retrieved articles and consulting with experts to identify landmark works. The final sample included 45 articles analyzed and synthesized using the matrix method. Results The results indicated a wide array of information systems were used by LHDs and supported diverse functions aligned with five categories: administration; surveillance; health records; registries; and consumer resources. Detail regarding specific programs being used, location or extent of use, or effectiveness was lacking. The synthesis indicated evidence of growing interest in health information exchange groups, yet few studies described use of data standards or standard terminology in LHDs. Discussion Research to address these gaps is needed to provide current, meaningful data that inform public health informatics research, policy, and initiatives at and across the LHD level. Conclusions Coordination at a state or national level is recommended to collect information efficiently about LHD information systems that will inform improvements while minimizing duplication of efforts and financial burden. Until this happens, efforts to strengthen LHD information systems and policies may be significantly challenged.